Perfluorooctanoic acid disrupts thyroid hormone biosynthesis by altering glycosylation of Na+/I− symporter in larval zebrafish - Zhenzhen Cai; Guangdi Zhou; Xiaogang Yu; Yatao Du; Qiuhong Man; Weiye Charles Wang (Ecotoxicology and Environmental Safety)
Perfluorooctanoic acid (PFOA) is a well-known thyroid disruptor that has been found to induce hypothyroidism. However, the exact molecular mechanism by which PFOA reduces thyroid hormone levels remains unclear. In this study, we have discovered that PFOA disrupts the glycosylation process of the sodium/iodide symporter (NIS), which inhibits the translocation of NIS onto the plasma membrane of thyroid follicular cells. Our results also demonstrate that PFOA disrupts thyroid stimulating hormone (TSH)-dependent signaling pathways involved in cellular glycosylation, impairing NIS glycosylation and reducing the ability of iodine uptake. This leads to an insufficiency of iodine for thyroid hormone production inside the follicular cells of the thyroid, resulting in lower-than-normal thyroxine levels detected in zebrafish larvae. These findings are consistent with our previously published data, which showed that PFOA induces neural behavior changes during the early stages of neuronal development in zebrafish. This new discovery provides valuable insights into the molecular characteristics of endocrine-disrupting chemicals (EDCs) that are known to affect the thyroid. It may also contribute to a better understanding of how altered glycosylation could be a potential risk factor for the association between exposure to specific per- and polyfluoroalkyl substances (PFAS) and various health effects in humans.